Effects of conventional interweaving and secondary deposition on the microstructure and properties of Ti6Al4V/AA2024 alloy component fabricated by laser-directed energy deposition - Dongqi Zhang; Dong Du; Ze Pu; Shuai Xue; Junjie Qi; Jiaming Zhang; Baohua Chang (Journal of Materials Research and Technology)
The connection of dissimilar materials has always been a great challenge, especially titanium alloy and aluminum alloy, which have broad application prospects in the aerospace industry. In this work, the Ti6Al4V/AA2024 alloy component was prepared by laser-directed energy deposition (L-DED) technology based on a conventional interweaving structure, and the microstructure of four typical position interfaces was analyzed. Aiming at the problem of poor forming quality of titanium alloy in the second interweaving layer caused by high laser reflectivity of aluminum alloy, a secondary deposition process was proposed. The microstructure and mechanical properties of Ti6Al4V/AA2024 alloy component fabricated by two different processes were characterized and tested. The problems of discontinuity and penetrating cracks at the Ti6Al4V layer in the second interweaving layer are effectively tackled by secondary deposition. As a result, the mechanical property of the deposited structure can be effectively improved, of which the average compressive shear strength is 8% higher than that of the conventional interweaving Ti6Al4V/AA2024 alloy component. The stress at the Ti6Al4V/AA2024 interface presents a zig-zag distribution because of the interweaving structure, which avoids the generation of continuous stress bands and effectively inhibits the interface crack propagation.